The constitutional building of the nation of the state in South Africa : unity and diversity - (:unkn) unknown (My University, 1998)
Since 1994, South Africa has created a new constitutional order to put a definitive end to apartheid. From now on, the constitutional ideal rests on the concept of unity in diversity, explicitly legally established in the preamble of the final constitution. Equality, nondiscrimination, the universality of citizenship, and the rights and freedoms (generally admitted in liberal democracies) are also legally established, making the principle of equality one of the cornerstones of the constitution. Now the idea of equality as well as the principle of national reconciliation goes hand in hand with the attempt of establishing and promoting national unity. The state, although decentralized, also is seeing its preeminence assured from the moment that the national interest justifies it. This will mean creating a new state nation. However, because of their cultural diversity, the South Africans can't accept unification if they must lose their separate identities. The communities’ demands have driven the government to take the multicultural character on the society into consideration. The republic of South Africa is officially multilingual. It recognizes the authority of the African Negro traditional chiefs, the customs and the rites practiced in the country, and the right to practice, individually or collectively, the culture, language and religion of one's choice. Moreover, whether on the cultural or political plan, the cultural communities don't benefit from a status of public law. They are not politically represented in this way, and can either inhibit the freedom of their members or discriminate against them. Cultural rights are thus recognized so the individual is able to express his or her identity. Therefore the state has for its mission statement to promote the unity and the diversity of this heterogeneous and multicultural society, for which unity cannot be realized without the acceptance of the diversity of the social body, which rests on the implici
Keywords: African Research